Evaluation of disinfection methods of orthodontic pliers Avaliação dos métodos de desinfecção de alicates ortodônticos - Camilla Machado Feitosa de Almeida; Adriana Silva de Carvalho; Danilo Antônio Duarte (Dental Press Editora, 2012)
INTRODUCTION: In recent years, a strong behavior change regarding the control of cross infection during dental treatment was perceived, except among some orthodontists who insist in the misconception that Orthodontics is a specialty of low risk in the transmission of infectious and contagious diseases. OBJECTIVE: The objective of this study was to evaluate the methods used by orthodontists for disinfection of pliers in their daily practice. METHODS: The bacteria Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus salivarius were inoculated in vitro in 30 orthodontic pliers. The pliers were divided into 3 groups (n = 10) and disinfected in different ways. Group 1: Brush, soap and water; Group 2: Cotton soaked in ethyl alcohol 70%; Group 3: Immersion in a solution of 2% glutaraldehyde for 30 minutes and then rinsed with water. RESULTS: The results showed that the ethyl alcohol 70% (Group 2) kept 20% of the pliers infected, being more efficient than the soap and water (Group 1), which maintained 60% of contaminated pliers. Only immersion in 2% glutaraldehyde was able to decontaminate all pliers and was statistically superior to the aforementioned methods (p = 0.030). CONCLUSION: Based on these results, we concluded that among the tested methods, disinfection of orthodontic pliers with 2% glutaraldehyde is the only efficient method. INTRODUÇÃO: nos últimos anos, constatou-se uma forte mudança de comportamento no que diz respeito ao controle de infecção cruzada durante atendimento odontológico, exceto dentre alguns ortodontistas, que ainda persistem na ideia equivocada de que a Ortodontia é uma especialidade de baixo risco na transmissão de doenças infectocontagiosas. OBJETIVO: objetivo desse trabalho foi avaliar os métodos mais usados pelos ortodontistas para desinfecção de alicates na sua clínica diária. MÉTODOS: as bactérias Pseudomonas aeruginosa, Streptococcus salivarius e Staphylococcus aureus foram inoculadas in vitro em 30 alicates ortodônticos. Os alicates foram divididos em 3 grupos (n=10) e desinfectados de formas diferentes: grupo 1, escova, água e sabão; grupo 2, algodão embebido em álcool etílico a 70%; grupo 3, imersão em solução de glutaraldeído a 2% durante 30 minutos sendo, em seguida, enxaguados com água corrente. RESULTADOS: os resultados demonstraram que o álcool etílico 70% (grupo 2) manteve 20% dos alicates infectados, sendo mais eficiente que a água e sabão (grupo 1), que mantiveram 60% dos alicates contaminados. Apenas a imersão em glutaraldeído 2% foi capaz de descontaminar todos os alicates, sendo estatisticamente superior aos outros métodos (p =0,030). CONCLUSÃO: com base nesses resultados, concluiu-se que, dentre os métodos testados, a desinfecção de alicates ortodônticos com glutaraldeído 2% é o único método eficiente.